Similar or different? On the use of digital platforms by young Muslims in Italy - Peruzzi, Gaia; Volterrani, Andrea; Lombardi, Raffaele (E|C, 2021)
The combination of media and migration is a classic theme of the social sciences. If migration is one of the most powerful factors in the transformation of societies, and the media are among the protagonists of the social construction of reality, then the narratives and media practices that natives and migrants produce starting from, and around, the migration experience are also fundamental agents of change. In a well-established panorama of studies, today two phenomena raise new questions: on the technological side, the massive spread of social networks and platforms; on the cultural side, the growth of the sons and daughters of migration, young people with migrant families, mixed backgrounds, often discriminated against their peers. The paper narrates the results of a survey, carried out in 2018-2019, on the relationship of Islamic youth with platforms and social network sites, to detect in their consumption practices similarities and differences with those of natives. To this end, 42 interviews were conducted with young men and women aged 18 to 30, residing in seven Italian cities.